ISOLASI DAN IDENTIFIKASI MORFOLOGI SPORA FUNGI MIKORIZA ARBUSKULA PADA DAERAH PERAKARAN BEBERAPA TANAMAN HORTIKULTURA DI LAHAN PERTANIAN DESA SIDERA - Samsi, Nur; Pataâdungan, Yosep; Thaha, Abd Rahim (AGROTEKBIS, 2017)
The aims of the study were to determine the existence and the number of spores, and         to determine the characteristics of spores morphology of arbuscular mycorrhiza fungi. The study was conducted on July to September 2015. Method used in this study was a descriptive explorative method with the purposive sampling to take a sample of the soil. While the process of this study covering : to get  permission used of location, field collection data, determination point to take soil sample, taking soil sample, analysis of the soil characteristics was done Laboratory, isolation of AMFspores and identification morphology of AMFspores. The results of the research showed thatthe highest spores population found in the onion rhizosfer, that were 344 spores / 10 g soil, while the lowest number of spores found in the tomatoes rhizosfer that were14 spores / 10 g soil. The characteristics of morphology AMFspores found were a round, oval and elips. The colour of spores ranging from the clear, yellow to brown and orange. Key Words : Arbuscular Mycorrhiza Fungi, horticulture, identification, isolation.